Spatial diversity of coral reef communities in Sulu Sea marine corridors - Licuanan, Wilfredo Roehl Y. (Animo Repository, 2008)
Most protected coral reefs and coral communities in the Philippines are in small fishery reserves chosen for their coral cover and fish biomass, rather than their biodiversity conservation value. In an effort to improve criteria for designing these small reserves, spatial arrangement, particularly patch sizes of the reef benthos, was examined using semivariograms computed from DCA ordination scores of raw data. The data were generated from reef photos taken at one-meter intervals along I 00m transect lines, deployed along depth contours at 27 reef sites in three locations in the Sulu Sea. These locations are along the Cagayan Ridge (including Cagayancillo, and the Tubattaha National Marine Park), and reefs in Balabac Islands, southern Palawan that lie in a strait connecting the Sulu Sea with the South China Sea. Three basic community types were discerned - Type I communities are made up mostly by sand, rubble, and macroalgae as typically encountered in reef flats and backreef areas; Type 2 communities are a mix of different forms of various coral genera (except Acropora); and Type 3 communities are made up mostly of Acropora, either in tabulate or branching form. These community types are typically seen as mosaics, but their relative proportions vary with depth and exposure to monsoon winds, and appear to indicate disturbance history of a site. Type I and Type 3 communities are typically large patches, with the latter at shallow sites, and the former at deep or sheltered ones. Community mosaics dominated by both types have low diversity, but the latter also has the highest coral cover. Type 2 communities, on the other hand, have small mosaic patches and steep species area curves. These are typically found at intermediate depths.